The Influence of the Marketing Mix on Consumer Satisfaction with La Fonte Spaghetti Pasta - Gandhy, Abel; Banjarnahor, Susi; Hardini, Sri (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The competition within the food sector has significantly increased, particularly in the spaghetti pasta product category. Numerous brands are competing in the market, necessitating effective marketing strategies for companies to maintain market share and boost product sales. This research aims to analyze the impact of the marketing mix (product, price, place, and promotion) on consumer satisfaction with La Fonte pasta spaghetti. The study employs a quantitative descriptive research method, utilizing both primary and secondary data sources. The population consists of individuals who have consumed La Fonte pasta spaghetti at least twice, with a sample size of 100 respondents selected through purposive sampling. The data analysis technique involves multiple linear regression using SPSS software. The results indicate that the marketing mix has a positive and significant impact on consumer satisfaction with La Fonte pasta spaghetti when considered collectively, as evidenced by a significant value of 0.000 < 0.005. However, when examined individually, the product, price, and place variables show positive but non-significant effects on consumer satisfaction, with significant values of 0.076 > 0.05. The study suggests improving the promotion variable, recommending the addition of promotional activities on social media platforms such as Facebook and Instagram.